Proceedings of International University Carnival on E-Learning (IUCEL) 2019 : 21 – 22 August 2019 DeTAR Putra, UNIMAS Kota Samarahan, Sarawak, Malaysia - Chen, Chwen Jen (UNIMAS Publisher, 2019)
The 2019 edition of International University Carnival on E-Learning (IUCEL) is held for the first time in the island of Borneo on 21 and 22 August 2019. Universiti Malaysia Sarawak (UNIMAS) is proud to be hosting the event. IUCEL acts as a platform to promote, explore, and share best practices and global expertise in e-Learning applications at all levels of learning institutions from all over the world. This year's theme "Inspiring Innovations for Sustainable Futures" signifies the call for future-proof practices and innovations that are impactful to the community at large.